Вегетативне розмноження Sophora japonica L. стебловими живцями - Shlapak, V.P.; Pukas, S.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
The data about vegetative reproduction of Sophora japonica L. have been presented. It was concluded, that green grafts better implanted in comparative with ligneous grafts. The results of reproduction with using of growth stimulator Emistym are better.